2006
DOI: 10.1007/s00330-006-0294-2
|View full text |Cite
|
Sign up to set email alerts
|

In vivo proton MR spectroscopy of primary tumours, nodal and recurrent disease of the extracranial head and neck

Abstract: Benign and malignant neoplasms as well as metastatic lymph nodes of 39 patients were examined using localized single voxel magnetic resonance spectroscopy (MRS) [repetition time (TR) 1500, echo time (TE) 135) at 1.5 T. New techniques with simultaneous correction of motion artefacts during the acquisition, three-dimensional saturation pulses, respiratory triggering and smaller volume of interest (VOI) size, were applied. Ratios of peak areas under the choline (Cho) and creatine (Cr) resonances were estimated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
20
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…The height of Cho peaks shown on in vivo single-voxel 1 H-MR spectroscopic images is believed to be related to increased cellular membrane phospholipid biosynthesis and is, therefore, considered as an active marker for cellular proliferation. 16 A number of studies with in vivo 1 H-MR spectroscopy have shown that Cho signals could be reliably found in most malignant tumors of the extracranial head and neck, such as squamous cell carcinomas, [6][7][8][11][12][13]17 salivary carcinomas, 9,12 and extracranial malignant lymphomas. 11,18 Soft-tissue and bone sarcomas (outside the head and neck) marked with Cho signals have also been reported.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The height of Cho peaks shown on in vivo single-voxel 1 H-MR spectroscopic images is believed to be related to increased cellular membrane phospholipid biosynthesis and is, therefore, considered as an active marker for cellular proliferation. 16 A number of studies with in vivo 1 H-MR spectroscopy have shown that Cho signals could be reliably found in most malignant tumors of the extracranial head and neck, such as squamous cell carcinomas, [6][7][8][11][12][13]17 salivary carcinomas, 9,12 and extracranial malignant lymphomas. 11,18 Soft-tissue and bone sarcomas (outside the head and neck) marked with Cho signals have also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9][10][11][12][13]17 However, some studies found that the Cho/Cr ratio could only be measured in half or less of extracranial head and neck neoplasms. [8][9][10][11] In our series, the peaks of Cr metabolites could only be identified in approximately 25% of masticator space lesions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cho containing compounds are identified in vivo as a spectral peak at 3.2 ppm using proton magnetic resonance spectroscopy ( I H-MRS), which is a technique that can be added easily to the routine magnetic resonance imaging (MRI) examination. Cho has been identified in a range of head and neck cancers including HNSCC (1)(2)(3)(4)(5)(6)(7)(8), where pretreatment cho levels correlate with histological grading (7) and posttreatment cho levels with the presence of residual/ recurrent cancer after surgery or chemoradiotherapy (8). Changes in cho ratios from pretreatment to posttreatment also have been reported.…”
mentioning
confidence: 99%